2020
DOI: 10.24252/eternal.v61.2020.a12
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Difficulties in Translating Narrative Text From English Into Indonesia at Iain Bukittinggi

Abstract: The research is due to several problems found in the field; the students assumed that narrative text was the difficult text to translate. It happened because the students translate the text literally, also the students were lack of vocabularies in translating the text. This research aims to find out the causes of students’ problems in translating narrative text. The research used descriptive method with a quantitative approach in which the sample of the research was 55 fifth semester students of English Educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Some students tend to focus on the lexical meaning and ignore the grammatical meaning, so they do not realize that some nouns in Vietnamese did not have equivalent terms in English. The results are very much aligned with many authors as mentioned above such as Hastuti et al (2020) in terms of linguistic factors, Idami et al (2022) in terms of fixed expressions, Noviyanti (2020) when talking about both linguistic and nonlinguistic factors causing translation difficulties, Cuc (2018) in terms of syntax and lexical choices, and Phan et al (2021) in terms of cultural aspects and long structures causing translation difficulties.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Some students tend to focus on the lexical meaning and ignore the grammatical meaning, so they do not realize that some nouns in Vietnamese did not have equivalent terms in English. The results are very much aligned with many authors as mentioned above such as Hastuti et al (2020) in terms of linguistic factors, Idami et al (2022) in terms of fixed expressions, Noviyanti (2020) when talking about both linguistic and nonlinguistic factors causing translation difficulties, Cuc (2018) in terms of syntax and lexical choices, and Phan et al (2021) in terms of cultural aspects and long structures causing translation difficulties.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, these participants were supposed to read more books in both Vietnamese and English to understand more the structures and cultural differences between the two languages. Hastuti, Kardena, and Chio (2020) found that the students studying an English Education Study program considered it is very difficult to translate narratives and they tended to do it literally. Moreover, insufficient vocabulary load caused them much challenge to cope with translating the texts.…”
Section: Related Studiesmentioning
confidence: 99%
“…As a result, when translating, one needs consideration to make certain changes in considering the context of the target language in order to generate effective and natural translation. A good translation should sound like the original text (Hastuti et al, 2020). In addition, Fadhillah et al (2019) said that the success of a translation greatly depends on the purpose of the translation itself; the results reflect the needs of the people who use the translation.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, teaching reading in most formal schools focused on how students can translate the texts and measure their comprehension through questions (Hastuti et al, 2020). Besides, Dickinson et al (2019) stressed that teaching reading should focus on an in-depth understanding of words form, use, and meaning.…”
Section: Introductionmentioning
confidence: 99%